1980
DOI: 10.1113/jphysiol.1980.sp013115
|View full text |Cite
|
Sign up to set email alerts
|

Specific features of smooth muscle cells recorded from the placental region of the myometrium of pregnant rats

Abstract: SUMMARYThe muscle membrane and contractile properties of placental and non-placental regions of pregnant and postpartum myometria of the rat were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
23
0
1

Year Published

1983
1983
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 18 publications
3
23
0
1
Order By: Relevance
“…correlates well with studies in the rat myometrium in which weak potentials, slow propagations, and a shorter length constant were found in microelectrode recordings (16). In the pregnant cat, extracellular recordings performed in vivo and in vitro showed that the placental region was less excitable and showed little or no spontaneous action potentials (6).…”
Section: Discussionsupporting
confidence: 58%
“…correlates well with studies in the rat myometrium in which weak potentials, slow propagations, and a shorter length constant were found in microelectrode recordings (16). In the pregnant cat, extracellular recordings performed in vivo and in vitro showed that the placental region was less excitable and showed little or no spontaneous action potentials (6).…”
Section: Discussionsupporting
confidence: 58%
“…These occur in either Krebs, Tyrode, or Locke solutions (OsA et al, 1974;OSA and KATASE, 1975;OSA and FUJiNo, 1978;KANDA and KURIYAMA, 1980;KAWARABAYASHI and MARSHALL, 1981). It was also confirmed that noradrenaline causes excitatory effects in Day 21 preparations, and inhibitory effects in Day 22 preparations.…”
Section: Discussionsupporting
confidence: 51%
“…The extent to which similar mechanisms occur in the myometrium remains to be determined. The electrical activity of myometrial cells from placental regions is suppressed compared with non-placental regions in the rat uterus (Kanda & Kuriyama, 1980) possibly due to locally acting placental progesterone (Csapo, 1961). It is possible, therefore, that the exposure of the myometrial expiants to the lower progesterone concentrations of the peripheral circulation might reduce an inhibitory action of this or any other hormones produced by intrauterine tissues, and lead to an increased frequency of contraction.…”
Section: Discussionmentioning
confidence: 99%